2021
DOI: 10.1186/s12889-021-11478-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of effluent management from university hospitals in the Littoral department in Benin

Abstract: Background Liquid discharges from hospitals (effluents) threaten the environment and are now a central concern of all stakeholders in the health system and those in the protection of the environment. The management of effluents is a major problem in developing countries. The objective of this study was to assess the quality of effluent management at the level of university hospital centers (CHU) in the Littoral region in Benin. Methods It was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In another study conducted in Benin in 2021 in the commune of Agbagnizoun, the bulk of biomedical waste is general waste (38%), followed by non-atomic infectious waste (24%), and sharp materials (5%) [11]. In the university hospitals of Cotonou in Benin in 2021, waste sorting was not performed in 51.9% of cases [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study conducted in Benin in 2021 in the commune of Agbagnizoun, the bulk of biomedical waste is general waste (38%), followed by non-atomic infectious waste (24%), and sharp materials (5%) [11]. In the university hospitals of Cotonou in Benin in 2021, waste sorting was not performed in 51.9% of cases [10].…”
Section: Discussionmentioning
confidence: 99%
“…We found that one agent out of two had access to waste garbage cans, 44% of the agents mentioned shortages of waste garbage cans or bags, and the main equipment available to handling personnel was gloves (98.8%). According to Todédji et al in 2021, in Cotonou hospitals, personal protective equipment (PPE) for maintenance workers was insufficient and the quantity of PPE available to the departments did not depend on the number of employees, with delays in supplying the departments sometimes resulting in stock-outs [10]. In the district hospital of Gaweye in Niamey in 2018, the note that the quality of availability and accessibility of inputs essential to the proper management of biomedical waste was 25 % with PPE of maintenance workers old and barely replaced [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospital wastewater (HWW) constitutes a much greater threat to the environment than urban effluent (Sanaa et al, 2019 ). The hospitals can use a considerable volume of water per day, which varies between 400 and 1200 L per day (Todedji et al, 2021 ), and therefore generate an important volume of wastewater, which is estimated between 400 and liter per day (Sanaa et al, 2019 ). These establishments are also known for the variety and high rates of wastewater pollution (Bouzid et al, 2021 ; Machkor et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%